2000
DOI: 10.2981/wlb.2000.023
|View full text |Cite
|
Sign up to set email alerts
|

Spring‐summer movements of male capercaillie Tetrao urogallus: A test of the ‘landscape mosaic’ hypothesis

Abstract: The 'landscape mosaic' hypothesis predicts that adult male capercaillie Tetrao urogallus track available habitat when making distinct seasonal migrations. We tested this hypothesis by comparing movement from leks to summer range in three geographical regions, viz. northwest Russia (Pechora), southwest Russia (Tver) and southeast Norway (Varaldskogen). All radio-collared males dispersed out of their daytime lek territories to an average distance of 2.3 km (±0.37) from lek centres (N = 52). In Russia, three bird… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The home ranges are large, about 100 hectares or more (Rolstad 1988, Rolstad et al 1988, and the area used by a lekking population covers several thousands of hectares (Hjorth 1994, Hjeljord et al 2000. There are also differences, for instance, in habitat use between the sexes (Rolstad and Wegge 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The home ranges are large, about 100 hectares or more (Rolstad 1988, Rolstad et al 1988, and the area used by a lekking population covers several thousands of hectares (Hjorth 1994, Hjeljord et al 2000. There are also differences, for instance, in habitat use between the sexes (Rolstad and Wegge 1990).…”
Section: Introductionmentioning
confidence: 99%
“…This means that, according to movement abilities of capercaillie (Hjeljord et al 2000), dispersal of this species across the Catalan landscape appears to be seriously hindered due to the very low chances of effective connections between forest habitat components. However, 35% of the total habitat area corresponds to one single connected region (with 183 nodes out of 522), and the class coincidence probability (CCP) (Pascual-Hortal and Saura 2006) equals 0.18 for the capercaillie habitat, where CCP is defined as the probability that two individuals randomly placed within the habitat are able to find each other (Jaeger 2000;Pascual-Hortal and Saura 2006), which occurs if they are placed within the same component.…”
Section: Resultsmentioning
confidence: 99%
“…Capercaillie average dispersal distance, obtained as a result of a spring-summer movements study with 52 radio-collared males (Hjeljord et al 2000), was found to be 2.3 km (±0.37).…”
Section: Study Area and Capercaillie Distributionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several authors have described seasonal range use patterns of capercaillie resulting from large-scale movements and changes in seasonally based resources , Storch 1995, Menoni et al 1997, Hjeljord et al 2000. Smaller-scale changes may occur on a daily and weekly basis as resources such as food plants fluctuate in availability (Odden et al 2003).…”
mentioning
confidence: 99%